Higher-Order Commutators of Parametric Marcinkiewicz Integrals on Herz Spaces with Variable Exponent - Hongbin Wang; Dunyan Yan (Journal of Function Spaces)
Let Ω∈Ls(Sn-1) for s⩾1 be a homogeneous function of degree zero and b be BMO functions. In this paper, we obtain some boundedness of the parametric Marcinkiewicz integral operator μΩρ and its higher-order commutator [bm,μΩρ] on Herz spaces with variable exponent.